The Influence of Bilectalism and Non-standardization on the Perception of Native Grammatical Variants - Leivada, Evelina; Papadopoulou, Elena; Kambanaros, Maria; Grohmann, Kleanthes K. (Frontiers in Psychology, 2017)
Research in speakers of closely related varieties has shown that bilectalism and non-standardization affect speakers’ perception of the variants that exist in their native languages in a way that is absent from the performance of their monolingual peers. One possible explanation for this difference is that non-standardization blurs the boundaries of grammatical variants and increases grammatical fluidity. Affected by such factors, bilectals become less accurate in identifying the variety to which a grammatical variant pertains. Another explanation is that their differential performance derives from the fact that they are competent in two varieties. Under this scenario, the difference is due to the existence of two linguistic systems in the course of development, and not to how close or standardized these systems are. This study employs a novel variety-judgment task in order to elucidate which of the two explanations holds. Having administered the task to monolinguals, bilectals, and bilinguals, including heritage language learners and L1 attriters, we obtained a dataset of 16,245 sentences. The analysis shows differential performance between bilectal and bilingual speakers, granting support for the first explanation. We discuss the role of factors such as non-standardization and linguistic proximity in language development and flesh out the implications of the results in relation to different developmental trajectories.